Reframing less conventional speech to disrupt conventions of "compulsory fluency": A conversation analysis approach - Duque, Camille; Lashewicz, Bonnie (Disability Studies Quarterly, 2018)
Our purpose is to illuminate compliances with, and resistances to, what we are calling "compulsory fluency" which we define as conventions for what constitutes competent speech. We achieve our purpose through a study of day-to-day communication between a woman with less conventional speech and her support providing family members and friends. Drawing from McRuer's (2006) compulsory ablebodiedness and Kafer's (2013) compulsory able-mindedness, we use "compulsory fluency" to refer to a form of articulation that is standardized and idealized and imposed on all speakers including those whose speech is less conventional. We see compulsory fluency as central to North American conceptions of personhood which are tied to individual ability to speak for one's self (Brueggemann, 2005). In this paper, we trace some North American principles for linguistic competence to outline widely held ideals of receptive and expressive language use, namely, conventions for how language should be understood and expressed. Using Critical Disability Studies (Goodley, 2013; McRuer, 2006) together with a feminist framework of relational autonomy (Nedelsky, 1989), our goal is to focus on experiences of people with less conventional speech and draw attention to power in communication as it flows in idiosyncratic and intersubjective fashion (Mackenzie & Stoljar, 2000; Westlund, 2009). In other words, we use a critical disability and feminist framing to call attention to less conventional forms of communication competence and, in this process, we challenge assumptions about what constitutes competent speech. As part of a larger qualitative study, we conduct a conversation analysis informed by Rapley and Antaki (1996) to examine day-to-day verbal, vocal and non-verbal communications of a young woman who self identifies as "having autism" - pseudonym Addison - in interaction with her support-providing family members and friends. We illustrate a multitude of Addison's compliances with, and resistances to, compulsory fluency to bring awareness to competence inherent in less conventional speech and we argue this illumination as a call for listening with greater care and more open expectations in efforts to understand, and participate in the expression of, meanings embedded in less conventional speech.